The Byzantine-Islamic transition in Palestine an archaeological approach - Avnî, Gidʿôn (Oxford Univ. Press, 2014)
Using recent archaeological findings, Gideon Avni addresses the transformation of local societies in Palestine and Jordan between the 6th and 11th centuries AD, arguing that the Byzantine-Islamic transition was a much slower and gradual process than previously thought
Includes bibliographical references and index
Keywords: Geschichte 500-1100; Palestine / Antiquities Byzantine; History; Geschichte; Islamisierung; Archäologie; Sozialer Wandel; Palästina